The use of brain lab navigator in the management of small deep seated brain tumors. - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: A comparism study for management of deep seated small brain tumors less than 4 cm in the 3 diameters between cases managed by Brain lab navigator and those without it.Patients and methods: We took 20 patients from the retrospecture data before the use of Navigator in our country compared with the 20 patients managed after the use of navigator in our hospital (specialized surgical hospital) in the neuro-surgical. Unit since 2002 till now. From 1/8/2002 till 31/12/2007 the study included the type of tumor & surgery & the result of surgery & time & complications ((morbidity & mortality)).Results: There was a significant increase of the safety of surgery by using the navigator including morbidity & mortality. But it was a time consuming procedure.Conclusion: The brain lab navigator is very useful safe device in the surgical management of deepseated small diameter less than 4mm. brain tumors.